Large blockholding and financial risk / Mas Nordiana Hj Rusli - Hj Rusli, Mas Nordiana (2013)
The objective of this study is to examine the relationship between large blockholding and financial risk. The regression analysis was performed on the sample of 571 firms listed in Bursa Malaysia for year 2012. The result of the study highlighted that financial risk was negatively related with large blockholdings. Since Malaysian capital market is rich with family business, examination on large family blockholders further seems to have similar results as large blockholdings. Similar result was also shown by institutional blockholding where it was found to be significantly inverse relationship with financial risk. This could be due to the reason that institutional shareholding provides better monitoring thus reducing the risk associated within the companies. On the other hand, government intervention through privatization was found to have strong relationship with financial risk. This result implies that government blockholders prefer higher financial risk as they are usually bailed out by the government in case of financial failure. The result of this study is robust after controlling the industries effects.